Using the MEAT VBP framework to analyse and understand the value of surgical gloves: An explanatory case study - Benedict Stanberry; Gerhard Bothma; Katie Harrison (Health Economics Review, 2021)
Background: Value-based healthcare is being extensively piloted, scaled and implemented by healthcare providers and systems around the world. However, the ability of the healthcare supply chain function to strategically contribute to the improvement of value has been held back by a lack of practical tools for turning value-based procurement from concept into action. Two recently developed conceptual models - the American CQO Movement and the European MEAT VBP Framework - have been developed to support the implementation of value-based procurement in healthcare. We demonstrate how the latter of these models can be adapted and applied pragmatically to generate insights into the value of a specific medical device, technology or consumable. Methods: We undertook an explanatory, qualitative, single-case study focused on a specific consumable - surgical gloves - that provide a critical example of a type of medical device usually procured in high volumes but at risk of commoditisation due to a widespread lack of understanding of their value. Since the global Covid-19 pandemic prevented fieldwork, structured interviews were conducted via Zoom and corroborated by a literature review. Results: We identified ten cost criteria and eight outcome criteria with which the value of surgical gloves can be analysed and understood. For each of these criteria we propose definitions and value impact metrics that decision-makers can use during a procurement exercise to describe, quantify and compare glove value. Conclusion: The MEAT VBP Framework provides a highly practical and adaptable means of imposing both structure and rigour on a value analysis process and of qualitatively describing the potential value impact of surgical gloves for patients, professionals, providers and health systems.
Keywords: 330; MEAT VBP Framework; Value-based procurement; Surgical gloves; Case study